Bearing capacity of mixed soil model - Mehdi Khodashenas Pelkoo; Abdoullah Namdar (Fracture and Structural Integrity)
The main objective of this research is improvement of red soil with addition of construction materials. This method could provide a scientific way to create a soil foundation with sufficient stability against geo-technical problems or instabilities. Laboratory tests have been conducted to assess the behavior of red soil, when amended with different types of gravels, soils and sand under compacted conditions with Optimum Moisture Content (OMC). Safe bearing capacity of all models, have been calculated to identify best and worst soil mixed model.